Regional Migration, Insurance and Economic Shocks: Evidence from Nicaragua - Teresa Molina Millán (Institute for the Study of Labor (IZA), 2015)
To test whether transfers sent and received by regional migrants serve an insurance role, this paper estimates the causal impact of income shocks at a migrant's origin and destination location on the bilateral transfer of funds. Using rainfall shocks in rural Nicaragua, I find that migrants aged 15-21 years provide unilateral insurance to their origin household. Distinguishing by destination and economic activity I show that the level of insurance increases when migrants and households are exposed to less correlated shocks. In addition, I find evidence of bilateral insurance among rural migrants exposed to rainfall shocks with low levels of correlation with respect to shocks occurring at origin.
Keywords: O12; O15; F24; R23; 330; internal migration; remittances; risk; insurance; inter-households transfers; weather shocks